1997
DOI: 10.1094/cchem.1997.74.5.594
|View full text |Cite
|
Sign up to set email alerts
|

Production of Textile Fibers from Zein and a Soy Protein‐Zein Blend

Abstract: Zein fibers were successfully prepared by a wet‐spinning technique from a zein suspension formulated with 15% zein, 60% water, 22% 0.4N sodium hydroxide, and 3% urea by weight. Tenacities were measured with an Instron machine, and flexibility was determined by noting the smallest diameter rod around which a fiber could be looped without breaking. After spinning, the tenacity of the zein fibers was improved by modification with several agents: acetic anhydride for acetylation, glutaraldehyde, and dialcohols for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 2 publications
0
28
0
2
Order By: Relevance
“…Being relatively heat-stable, zein has proven to be a good candidate for hot melt extrusion (12,13), which is a thermal processing that is being increasingly adopted for the preparation of pharmaceutical solid dispersion based formulations. It has been reported that zein's structure only begin to change at temperatures above 120°C, which is likely to be due to protein cross linking by disulfide bonds (9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Being relatively heat-stable, zein has proven to be a good candidate for hot melt extrusion (12,13), which is a thermal processing that is being increasingly adopted for the preparation of pharmaceutical solid dispersion based formulations. It has been reported that zein's structure only begin to change at temperatures above 120°C, which is likely to be due to protein cross linking by disulfide bonds (9).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that zein's structure only begin to change at temperatures above 120°C, which is likely to be due to protein cross linking by disulfide bonds (9). The use of extrusion techniques to process zein is well known in the food industry (12,13), but the potential for the preparation of pharmaceutical products has not been widely explored. The aim of this work is to develop new oral controlled release caplets with tuneable release rates with zein as the sole excipient using a simple two-step processing, hot melt extrusion (HME) in combination with injection moulding (IM).…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades researches have focused on different spinning methods (Huang et al, 1995), on new fibres from soybean proteins and polyvinyl alcohol (Zhang et. al., 1999, Li, 2007 or zein proteins (Zhang et al, 1997), on new economical biochemical processes that modify physical structure of soya proteins, and on new solvents (Zhang et al, 2009). The experimental soybean protein fibres were made from two macromolecular components combined together into: -biconstituent fibres, where a spinning dope was prepared from a homogeneous mixture of two solutions -a soybean protein water solution and a water solution of synthetic polymer polyvinyl alcohol or cellulose or zein proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Fibres were made by dry spinning method. The optimum soy protein-zein blended fibre was made from a suspension containing 80% of soybean protein and 20% of zein in glycerol (Zhang et al, 1997), but the tenacity was only 0.20 cN/dtex. Another idea to improve low tensile strength and decrease shrinkage in boiling water was using water-soluble polymer, such as polyvinyl alcohol (PVA).…”
Section: Pure Soybean Protein Fibres From the Mid-twentieth Centurymentioning
confidence: 99%
“…Although soyprotein-and zein-based fibers with strength and breaking elongations similar to those of wool have been reported during the 1940s, neither the soyprotein nor the zein fibers with properties reported during the 1940s have been produced lately. 12,[15][16][17][18][19]33 The Young's modulus and moisture regain of wheat gluten fibers are similar to those of wool, and, therefore, products made from wheat gluten fibers should be soft and flexible as wool if similar denier fibers are used. No reports are available on the modulus of 100% soyprotein and zein fibers.…”
Section: Resultsmentioning
confidence: 99%